2020
DOI: 10.34739/zn.2019.48.04
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative investigation into consumer motivations and attitudes towards research shopping in the Georgian market

Abstract: This study aims to discover different levels of research shopping behavior among Georgian consumers. It adopted a deductive approach by selecting the relevant models of customer behaviour from past papers and testing them in the Georgian market. In order to find the main themes associated with research shopping, five focus groups were held using exploratory and semi-structured questions. The responses were analyzed on the basis of two main customer motivations, utilitarian and hedonistic, in order to find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, some papers discussed the customers and their purchasing patterns in the market which can shed more light on the effectiveness of interdepartmental synergy among the Georgian customers. Khoshtaria and Matin (2019) found that price, convenience and quality of products and services affect the switching behaviour among the Georgian customers. Their findings indicate a retailer with lower costs of operation or value added products and services are more successful to attract and retain customers in the country.…”
Section: The Frequency Of Visits and Monetary Value Spent By Customersmentioning
confidence: 99%
“…However, some papers discussed the customers and their purchasing patterns in the market which can shed more light on the effectiveness of interdepartmental synergy among the Georgian customers. Khoshtaria and Matin (2019) found that price, convenience and quality of products and services affect the switching behaviour among the Georgian customers. Their findings indicate a retailer with lower costs of operation or value added products and services are more successful to attract and retain customers in the country.…”
Section: The Frequency Of Visits and Monetary Value Spent By Customersmentioning
confidence: 99%
“…The reliability of the research model and constructs was tested using Cronbach`s alpha. The threshold for accepting the reliability was set at 0.7 (Khoshtaria 2016;Matin 2020;Matin et al 2020).…”
Section: Reliability Of Measuresmentioning
confidence: 99%